Cell specific effects of glucocorticoid treatment on the NF-κBp65/IκBα system in patients with Crohn’s disease - Thiele, Kirsten; Bierhaus, Angelika; Autschbach, Frank; Hofmann Bowman, Marion; Stremmel, Wolfgang; Thiele, Hanshelmut; Ziegler, Reinhard; Nawroth, Peter Paul (Gut, 1999)
Glucocorticoid treatment is known to reduce nuclear factor-kappa B (NF-κB)p65 binding activity and activation in lamina propria cells of patients with Crohn’s disease. However, lamina propria cells of glucocorticoid treated patients did not show increased expression of IκBα, and the hypothesised upregulation of IκBα by glucocorticoid treatment has not yet been shown in vivo. To investigate whether cells other than lamina propria localised mononuclear cells contribute to increased IκBα, resection gut specimens from patients matched for Crohn’s disease activity index (CDAI) with or without glucocorticoid treatment were studied, and changes in the NF-κB/IκBα system were determined in the lamina propria as well as in underlying submucosal and endothelial cells.
Gesehen am 09.06.2021